Physicochemical regularities of a high-voltage electroporcelain formation with a sintering temperature of 1200 °C - Bohdanova, K.B. (Functional Materials, 2018)
The composition and technological parameters of manufacturing low-temperature electroporcelain with complex of high electrophysical and mechanical properties have been developed. With the use of differential thermal, X-ray phase, IR spectroscopic and electron microscopic methods of analysis, physicochemical regularities in the formation of electrical porcelain at 1200°C have been established. It is shown that high dielectric and mechanical characteristics of low-temperature porcelain (ρV = 4.1·10¹⁴ Ohm·cm; E = (29-30) kV·mm⁻¹; tgδ·103 = 12.11; σr = 31 MPa) are provided by activating the sintering with the participation of a modified feldspar melt and intensive formation of the mullite phase in the form of microfibers with a predominant size of ~ 0.007-8 &mu>m with the addition of complex mineralizer additives (12 wt.% pyrophyllite and 0.3 wt.% titanium dioxide).